Assessing the thermal cracking process of coal in high-temperature environment: an ultrasonic approach - Junjun Feng; Junjun Feng; Shigeng Li; Chuanhua Xu; Jun Peng; Qisong Huang (Frontiers in Earth Science)
Thermal cracking of coal in high-temperature environments poses a significant challenge to the sustainability of deep coal mining. It increases the risk of coal and gas outbursts and spontaneous combustion and also contributes to groundwater pollution and greenhouse gas emissions, ultimately undermining the environmental sustainability of coal mining. This study investigates the coal thermal cracking in such environments and introduces an ultrasonic approach to evaluate the thermal cracking process. The results indicate a positive correlation between crack opening and cumulative moisture desorption, as well as between crack expansion rates and moisture desorption rates. In addition, the ultrasonic P-wave shows a robust response to both moisture desorption and thermal cracking, supported by nonlinear and linear models correlating wave velocity and attenuation coefficient, respectively. In addition, a theoretical model elucidates the driving forces, including surface tension and vapor pressure, that contribute significantly to thermal cracking at high temperatures. The ultrasonic method based on the theoretical model provides an innovative approach for assessing the coal thermal cracking process, contributing to improved environmental sustainability in deep coal mining.